Sob as águas do Rio Sergipe: relação comercial e marítima do porto de Santo Amaro das Brotas/SE a partir do tráfico interno de escravos no século XIX - Santos, Luciana de Souza (2014)
The reflection of this monograph are centered on a discussion related of the port City of Santo Amaro Das Brotas in Sergipe, one of the small states of Brazil, where the internal traffic of slaves on XIX century, as well as understandthe commercial relationship and sea. For both happen a discursive analysis an Historical Archeology, Maritime, Port on the port. For completion of the study it was decide by a field research that correlates data oral and theoretical content. For the collect oral speakers was utilized a tool structure interview, with a freedom enough for the people who can speak about it ,and expose their memories relationated at the period of construction of the Port,the slave and the important thing about the internal traffic of slaves. Considering the importance of slave labor for the heyday of sugar mill in Sergipe, this port during the beginning to the XIX century, was paramount importance to the local economy.It was evident that it was a port with sufficient spaces and sizes. The viability Maritime and economic was installed the first Custom House in Sergipe on this season.